Research Progress of High-Sensitivity Perovskite Photodetectors: A Review of Photodetectors: Noise, Structure, and Materials - Li, Guoxin; Wang, Yukun; Huang, Lixiang; Sun, Wenhong (ACS applied electronic materials, 2022)
In recent years, perovskite materials have been widely used in optoelectronic components due to a series of advantages such as a high light absorption coefficient, high carrier mobility, long carrier diffusion length, shallow defect level, and high crystallinity. The photodetector is an important photoelectric device that can convert light radiation signals into electrical signals, so it has significant applications and scientific research value in military, civil, and other fields. Semiconductor materials are an essential part of photodetectors. So far, many semiconductor materials have been used in photodetectors, including silicon, carbon nanotubes, III–V compounds, and quantum dots, and remarkable progress has been made in improving the light detection performance and device structure design. However, photodetectors based on these materials usually require expensive materials, rigorous processes, and complex manufacturing conditions, which hinder their commercial application. Optoelectronic devices based on perovskite materials have the advantages of a simple fabrication process, low cost, and high performance, making them widely considered in optoelectronic applications. This review focuses on the preparation and photoelectric performance of the perovskite photodetector and the effect of noise on the performance of the perovskite detector and how to reduce the detector’s noise to increase the detection rate. In this review, we mainly discuss the following four aspects of work. First, we discuss the various noises of perovskite photodetectors. Then, we explore ways to reduce the noise of perovskite detectors with different structures (photoconductor, photodiode, and phototransistor). We explore corresponding improvement methods for different device structure detectors to reduce noise and improve the detection performance. Next, we discuss the different synthesis methods of all-inorganic perovskites, including solution processing synthesis, vapor-assisted solution synthesis, and chemical vapor deposition. Finally, current challenges of perovskite photodetectors (toxicity, stability, flexibility, and self-powered) are summarized and prospected.